Existence and uniqueness of solutions for a class of infinite-horizon systems derived from optimal control - Lianwen Wang (International Journal of Mathematics and Mathematical Sciences)
This paper deals with the existence and uniqueness of solutions for a class of infinite-horizon systems derived from optimal control. An existence and uniqueness theorem is proved for such Hamiltonian systems under some natural assumptions.